Pliss na teraz daje naj.


a ) (2x - 1) + (3x - 2) - (4x - 6)
b) ( - y + 4) - (2y - 1) + (3y + 3)
c) (4a - 5) - (5a + 4) + (2a + 1)
d ) (x - 5) - (2x - 1) -(- x + 4)
e) (x - 4y + 1) - (x + 3y - 4) + (3x - y + 5)
f) (x - 3y + 1) - (x + 2y - 3) + (3x - y + 2)
g) (x + 2y - 1) - (3x - y + 5) + (2x - 3y + 4)
h) (8x - y) - (3x + y) - (-5x 2y)
I) 0 - (4a - b - 1) -(-5a - b + 1)​



Odpowiedź :

Odpowiedź:

a)(2x-1)+(3x-2)-(4x-6)=2x-1+3x-2-4x+6=x+3

b)(-y+4)-(2y-1)+(3y+3)=-y+4-2y+1+3y+3=2y+7

c)(4a-5)-(5a+4)+(2a+1)=4a-5-5a-4+2a+1=a-8

d)(x-5)-(2x-1)-(-x+4)=x-5-2x+1+x-4=0

e)(x-4y+1)-(x+3y-4)+(3x-y+5)=x-4y+1-x-3y+4+3x-y+5=3x-7y+10

f)(x-3y+1)-(x+2y-3)+(3x-y+2)=x-3y+1-x-2y+3+3x-y+2=

3x-6y+6

g)(x+2y-1)-(3x-y+5)+(2x-3y+4)=x+2y-1-3x+y-5+2x-3y+4=

-2

h)(8x-y)-(3x+y)-(-5x....nie wiem co tu za znak

i)0-(4a-b-1)-(-5a-b+1)=0-4a+b+1+5a+b-1=a+2b